A graph-based framework towards trading financial markets - Pretorious, Joshua Chance (Stellenbosch : Stellenbosch University, 2025)
Pretorious, J. C. 2025. A graph-based framework towards trading financial markets. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0d922223-6289-4084-b528-f1effce6b0f8